Encryption Of Internet Of Things Constrained Device For Digital Envelope: A Systematic Literature Review - Insan, Isa Mulia; Samopa, Febriliyan (IPTEK The Journal for Technology and Science, 2023)
Not only the exchange of information between IoT devices but integration between IoT devices and cloud servers has also brought IoT to a higher level. Security is the main problem for IoT devices with limited resources for exchanging information. Digital envelopes are one method that uses encryption to secure data. However, limited resources on constrained devices necessitate selecting the proper encryption. This systematic literature review (SLR) was conducted on 11 of 43 studies that have used encryption algorithms for IoT devices. In addition to using the algorithm, it will also explain the device used and the safety factor. A suitable encryption algorithm for the digital envelope has been found. In addition, Some of the safety factors, IoT devices, and specifications are also shown.